1999
DOI: 10.1093/gerona/54.3.m157
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Psychosis and Depression to Behavioral Disturbances in Geropsychiatric Inpatients With Dementia

Abstract: Both depressive and psychotic symptoms were associated with overall behavioral disturbances in patients with dementia. Psychotic symptoms and depressive symptoms were associated with different types of behavioral disturbances. Our findings support the contention that underlying depression or psychosis may partially account for different behavioral disturbances and that not all behavioral disturbances should be globally labeled "agitation." Future studies should address symptom-specific treatment of behaviorall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2001
2001
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
16
1
1
Order By: Relevance
“…They felt that this may be because residents with mild impairment are better able to communicate their needs and their depressed mood than residents with severe dementia. Other studies have evaluated patients admitted to an inpatient psychogeriatric unit (Kunik et al, 1999) and patients enrolled in an outpatient dementia evaluation and treatment clinic (Lyketsos et al, 1999). In a study of 208 patients with dementia admitted to a psychogeriatric unit, Kunik et al (1999) found that verbal and physical aggression were not correlated with depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They felt that this may be because residents with mild impairment are better able to communicate their needs and their depressed mood than residents with severe dementia. Other studies have evaluated patients admitted to an inpatient psychogeriatric unit (Kunik et al, 1999) and patients enrolled in an outpatient dementia evaluation and treatment clinic (Lyketsos et al, 1999). In a study of 208 patients with dementia admitted to a psychogeriatric unit, Kunik et al (1999) found that verbal and physical aggression were not correlated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have evaluated patients admitted to an inpatient psychogeriatric unit (Kunik et al, 1999) and patients enrolled in an outpatient dementia evaluation and treatment clinic (Lyketsos et al, 1999). In a study of 208 patients with dementia admitted to a psychogeriatric unit, Kunik et al (1999) found that verbal and physical aggression were not correlated with depression. Depression was rated by the Hamilton Depression Rating Scale (HDRS) and agitation was measured by the Cohen-Mans®eld Agitation Inventory.…”
Section: Discussionmentioning
confidence: 99%
“…Under the current de®nition, BPSD refers to a collective cluster of behavioral manifestations found in patients with dementia. However, the relationships between different behavioral domains have not been well de®ned (Frisoni et al, 1999;Kunik et al, 1999;Teri et al, 1999;Trabucchi et al, 1999). Individual symptom may be dependent on one another.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic symptoms in patients with AD are listed in table 1. Delusions occur in approximately 30-40% of patients with AD [7][8][9], fluctuate over time but often persist [10,11], and are associated with aggressive behavior [12][13][14][15] and rapid cognitive decline [9]. Hallucinations occur in approximately 5-20% of patients with AD [8,10,16,17], although the proportion varies considerably across studies.…”
Section: Psychosis In Admentioning
confidence: 99%